Teachers Views' On Awareness of Environmental Acquiring in Informal Learning Environments: The Sample of Kocaeli Science Houses) - Cavus, Ragip; Umdu Topsakal, Unsal; Oztuna Kaplan, Aysun (PEGEM AKAD YAYINCILIK EGITIM DANISMANLIK HIZMETLERI TIC LTD STI, 2013)
The aim of this study is to determine the teachers' view about getting students be aware of awareness of environmental according to the activities in Science Houses. 15 Science and Technology teachers working in Kocaeli Science House participated to the search which has been carried out in 2011 - 2012. In this research fenomological approach has been applied. Purposeful sampling is used. Semi-structure interviews and open-ended question forms which were prepared by the researchers and checked by experts were applied as data collection tools. Content analysis method is used for data analyzing. Teachers who participated in this study emphasized the importance of out of school learning environments and also Science Houses' activities for awareness of environmental. Furthermore they added that formal and informal learning activities should be together and teachers should take students to the out of school learning environments. When the literature is examined it is seen that informal and formal leaning areas are both important for awareness of environmental. In this research views of teachers working in out of school learning environments about the activities and students' awareness of environmental are investigated according the literature. As a result of this study it is found that out of school learning environments are important for awareness of environmental and these areas and their activities should be increased. It is hoped that this research will help the investigators who want to study about out of school learning environments.
Keywords: Environmental Education; Awareness of Environmental; Informal Learning; Out of School Learning Environments; Science Houses; Education & Educational Research